Consideration of custom (ʿUrf) by the Izalah Organization in Gombe, Nigeria: a critical examination = (مراعاة آلية "العرف" لدى جماعة الإزالة في ولاية غونبي، نيجيريا: دراسة نقدية) - Aishatu, Abubakar Kumo; Haneef, Sayed Sikandar Shah; Zakariyah, Luqman (IIUM Press, International Islamic University Malaysia, 2018)
‘Urf in the Sharīʿah serves as an essential tool for dealing with mu‘ᾱmalāt aspects of Muslim life. The ‘urf rulings stipulated by the scholars determine its acceptability or otherwise. A certain ‘urf serves as a legal principle to conduct a transaction in social interaction. However, Jamᾱ’atu Izalatil bid’a wa Iqᾱmatis Sunnah (The Society for the Removal of Innovation and Establishment of the Sunnah) uses the term bid‘ah indiscriminately to include some customary practices in mu‘ᾱmalāt. This leads to a different perception of how people understand the word and its application, which gives a different dimension of interpretation on the Sharīʿah allowance of ‘urf usage. Thus, depicting ʿurf as bid‘ah complicates the ability to verify the crux of bid‘ah in matters pertaining to ‘ibᾱdah and mu‘āmalāt in their respective domains. The results of the qualitative research conducted in Gombe metropolis show the people’s understanding and utilization of the words to be synonymous. This is a result of the Izalah organization’s application of the two words (bidʿah and ʿurf) in dealing with mu‘āmalāt as well as ʿibᾱdah. Muslims misunderstood the utilization of these terms and therefore misapply some practical Sunnah in marriage celebrations, for example, as bidʿah. Therefore, there is need for the organization to educate Muslims on the validity of customary practices that do not contravene the teachings of Islam.